Improvement of primary care for patients with chronic heart failure: a pilot study - Grol Richard; Wensing Michel; van Lieshout Jan (BMC, 2010)
Abstract Background Many patients with chronic heart failure (CHF) receive treatment in primary care, but data have shown that the quality of care for these patients needs to be improved. We aimed to evaluate the impact and feasibility of a programme for improving primary care for patients with CHF. Methods An observational study was performed in 19 general practices in the south-eastern part of the Netherlands, evaluation involving 15 general practitioners and 77 CHF patients. The programme for improvement comprised educational and organizational components and was delivered by a trained practice visitor to the practices. The evaluation was based on case registration forms completed by health professionals and telephone interviews. Results Management relating to diet and physical exercise seemed to have improved as eight patients were referred to dieticians and five to physiotherapists. The seasonal influenza vaccination rate increased from 94% to 97% (75/77). No impact on smoking was observed. Pharmaceutical treatment was adjusted according to guideline recommendations in 12% of the patients (9/77); 7 patients started recommended medication and 2 patients received dosage adjustments. General practitioners perceived the programme to be feasible. Clinical task delegation to nurses and assistants increased in some practices, but collaboration with other healthcare providers remained limited. Conclusions The improvement programme proved to have moderate impact on patient care. Its effectiveness should be tested in a larger rigorous evaluation study using modifications based on the pilot experiences.